RANCANG BANGUN ALAT PEMBERSIH SEKAT PURUN - RAHMAYANI; Rahmat Wahyudi; Muhammad Nalvin Rizkiandra; Dedy R Harahap (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Purun is one of the most widely used plants in daily life, such as weaving, crafts, straws and others. The process of preparing the purun is still done manually one by one with a puncture using an iron rod with a diameter of 2-3 mm. In order for the process of repairing the purun bulkhead to be faster, it is necessary to design a tool that helps repair the purun bulkhead to the purun straw. The design of the purun bulkhead cleaning device refers to the VDI 2222 design methodology which has 4 stages, namely, conceptualizing, designing, and organizing plans. The results of the process of repairing this tool can clean as many as 12 sticks of purun rods per process. Within 5 seconds the condition of the purun bulkhead after being released is 100% detached from the purun stem. With this tool, the purun repair process can be faster with maximum skating repairs.